Tender Bonds: Determinants, Procedures and Implications for Credit Guarantee Funds - Sobolewski, Dariusz (Journal of Finance and Financial Law, 2021)
The purpose of the article is to outline a new procedure that will enable economic operators to increase their access to tender bonds provided by funds for credit guarantees which are among the non-monetary forms of submitting a deposit in public procurement procedure. Methodology used to present the topic and to achieve the goal of the article is mainly based on the expertise and professional experience of the author. Results of the research outline that despite being properly established in Polish law, tender bonds have as yet been scarcely applied by economic operators requesting to participate in public contract award procedures. Moreover, the majority of credit guarantee funds focus on providing this type of sureties, with the consequence being an increasingly declining share of credit sureties and changes in these funds’ business profile. In order to continue this increase in tender bond sale, credit guarantee funds need to modify their existing procedures so as to make this type of security more popular among economic operators.